A Multimediation Model of Learning by Exporting: Analysis of Export-Induced Productivity Gains. (September 2017) - Tse, Caleb H.; Yu, Linhui; Zhu, Jianjun
This paper "opens a black box" in examining how and under what conditions do firms achieve productivity gains by exporting, conventionally known as the learning-by-exporting (LBE) effect. We extend the current theoretical paradigm by proposing that exporters utilize strategic decisions pertinent to innovativeness, production capability, and human capital so as to leverage knowledge and resources obtained from exporting in order to achieve productivity gains. We test and validate our hypotheses with panelized data of roughly 250, 000 Chinese firms over a 7-year period (2001-2007). We also show that the salience of these mediation mechanisms is contingent upon ownership structure and industry characteristics: Non-state-owned enterprises and firms in industries with medium export intensity or medium and high new product development intensity effectuate more learning through these conduits than their counterparts. The multimediation mechanism LBE model offers useful implications for academia, practitioners, and policy makers.